Ultra-broadband all-OPCPA petawatt facility fully based on LBO. (2020) - Galletti, Mario; Oliveira, Pedro; Galimberti, Marco; Ahmad, Munadi; Archipovaite, Giedre; Booth, Nicola; Dilworth, Emerald; Frackiewicz, Andy; Winstone, Trevor; Musgrave, Ian; Hernandez-Gomez, Cristina
Abstract: A petawatt facility fully based on noncollinear optical parametric chirped pulse amplification (NOPCPA) technology, Vulcan OPPEL (Vulcan OPCPA PEtawatt Laser), is presented. This system will be coupled with the existing hybrid-CPA/OPCPA VULCAN laser system (500 J, 500 fs beamline; 250 J, ns regime beamline) based on Nd:glass amplification. Its pulse duration (20 times shorter) combined with the system design will allow the auxiliary beamline and its secondary sources to be used as probe beams for longer pulses and their interactions with targets. The newly designed system will be mainly dedicated to electron beam generation, but could also be used to perform a variety of particle acceleration and optical radiation detection experimental campaigns. In this communication, we present the entire beamline design discussing the technology choices and the design supported by extensive simulations for each system section. Finally, we present experimental results and details of our commissioned NOPCPA picosecond front end, delivering 1.5 mJ, 180 nm (1/ e 2 ) of bandwidth compressed to sub-15 fs.